THE QUALITY OF DENTAL CARE SERVICES PROVIDED BY THE PRIVATE OFFICES IN IASI - PILOT STUDY RESULTS - Elena Mihaela Carausu; Cristina Gena Dascalu; Iulian Costin Lupu; Daniela Anistoroaei; Georgeta Zegan (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study was to identify the degree of satisfaction of patients about quality of the private dental medicine practices from Iasi, Romania. Material and methods. The authors of this study tested a representative sample of the population, consisting of 144 people, with different professions and ages. The data collection tool was an original questionnaire. Through its administration, it was intended to assess the patient's satisfaction with the dental care they received in different dental offices in Iasi during year 2018. Results. The results of the study show that 74.31% of the total patients surveyed are satisfied with the clinical quality of the dental care received, and 18.06% of them are worried about the high prices. The questioned patients believe that dentists with private practice have the necessary equipment and materials to provide dental services at the proper quality. Conclusions. Our study offers useful information for quality management of dental medicine services provided to the local population.